MENERAPKAN METODE SNOWBALL THROWING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VII-E SMPN 3 WARU: MENERAPKAN METODE SNOWBALL THROWING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VII-E SMPN 3 WARU - Linda Anisa; Retno Danu Rusmawati (Universitas PGRI Adi Buana Surabaya, 2015)
The subject of this research was the seventh grade students 2014/2015 academic year. The number of participants in this research was 36 students, there are 16 boy students and 20 girl students. In completing the research, the researcher used the observation,teacher and students activity, written test and field note as the instruments of collecting the data. The result of this research on pre-cycle or first reading skill comprehension condition of students acquire three students can be done with 8,32% on the class that consist 50,05. On the second cycle in the teacher activity was 83,3%; and students activity was showed 85,4%; the result test of students reading skill comprehension was 27,78% and the average was 74,78. The second cycle result was 16,7% which is higher than first cycle. In the teaching activity that shows has improved about 6,96% to 92,36%; the result of reading skill comprehension test based on SKL was 94,44% improve about 66,66%. In other hand, the average of study reading skill comprehension higher than before was 9,41% improve to 84,19. This research was improving students reading skill of Junior High School 3 Waru. Through reading comprehension, students were indirectly recognize and memorize learning material.